Do Entrepreneurs Really Earn Less? - Alina Sorgner; Michael Fritsch; Alexander Kritikos (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
We compare, based on German data, the income of self-employed individuals with and without employees with the income of dependently employed individuals. Our results show that self-employed with employees tend to earn significantly higher incomes than their salaried counterparts, while with the exception of solo-entrepreneurs without vocational degree - the income of solo self-employed tends to be significantly lower than that of comparable employees. We also observe that self-employed people are able to improve their earnings within the first three years after start-up, when we compare their actual earnings to their income before the start-up.
Keywords: L26; D22; D31; 330